Hizib and Wafaq: Magical Symbols that Bring to Life the Tariqa Tradition in West Java - Yunus, Badruzzaman M.; Zulaiha, Eni (UIN Sunan Gunung Djati Bandung, 2025)
This study explores the use of magical symbols within the Tariqa community in West Java, which faces accusations of deviation and conflict with the Takfiri group. Understanding this issue is crucial for mediating conflicts and promoting religious moderation in Indonesia. The research employs a qualitative descriptive approach, focusing on the Idrisiyyah-Tasikmalaya, Tijaniah-Garut, and Shadziliyyah tariqas. Data is analyzed using a semiotic model, examining magical symbols, their meanings, and practitioners' spiritual experiences. Data collection involves purposive sampling through interviews and field observations. Overall, the use of magical symbols is deemed legitimate within Islamic law and does not signify deviation or impurity.